B cell repopulation trajectory after rituximab treatment in autoimmune diseases: a longitudinal observational study - Nie, Yuxue; Li, Jingna; Wu, Di; Yang, Yunjiao; Zhang, Li; Bai, Wei; Jiang, Nan; Qiao, Lin; Huang, Can; Zhou, Shuang; Tian, Xinping; Li, Mengtao; et al. (Clinical and experimental medicine, 2023)
To investigate B-cell repopulation trajectory and the associated factors in patients with autoimmune diseases (AIDs) who underwent rituximab (RTX) treatment. This is a retrospective study in a large tertiary medical center. Kaplan–Meier analysis and Cox regression were used to investigate factors associated with B-cell repopulation. Latent class trajectory modeling (LCTM) was employed to identify distinct B-cell repopulation trajectory longitudinally. A total of 224 patients were included, with a cumulative follow-up time of 193.6 person-years. Patients with antineutrophil cytoplasm antibody-associated vasculitis (AAV), connective tissue disease, and IgG4-related disease exhibited significant differences in B-cell repopulation time ( p = 0.0055 by log-rank test). Multivariate Cox regression identified that higher levels of IgA (HR 1.21, 95%CI 1.01–1.45, p = 0.040) and concurrent glucocorticoid use (HR = 0.37,95%CI 0.20–0.67, p = 0.001) were associated with B-cell repopulation. The cluster showing prolonged B-cell depletion, identified by LCTM, had lower proportions of male (27% vs. 48.5%, p = 0.033), smoke history (17.6% vs. 38.7%, p = 0.025), higher proportions of AAV (44.3% vs. 15.2%, p = 0.004), RTX dose ( p = 0.042), history of cyclophosphamide use (70.4% vs. 48.5%, p = 0.003), meanwhile glucocorticoid use (94.8% vs. 72.7%, p = 0.001). The trajectory of B-cell repopulation after RTX infusion in AIDs was heterogeneous. Certain factors were associated with B-cell repopulation, and a specific cluster of patients demonstrated prolonged B-cell depletion after RTX treatment.